2020
DOI: 10.1002/jip.1556
|View full text |Cite
|
Sign up to set email alerts
|

The effects of liking on informational elements in investigative interviews

Abstract: The efficacy of principles of persuasion and influence in aiding uncooperative individuals to become more cooperative has been well documented in the basic science literature. Less known is their effects in investigative interviews. This study examined the effects of liking (positivity) on informational elements produced in investigative interviews. Interviewees participated in a mock theft experiment and were randomly assigned to tell the truth or lie about the potential theft. Half the interviews were conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 32 publications
(66 reference statements)
1
8
1
Order By: Relevance
“…After exiting that room and waiting, participants were escorted to a separate room in which a second, longer investigative interview occurred. 3 There were consequences to being believed and manipulation checks verified that participants were emotionally elevated during the experiment (differentially for truthtellers and liars) and that the stakes were perceived on a moderate-high level in all studies (for more information see Hwang & Matsumoto, 2020;, 2018b, 2019b.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…After exiting that room and waiting, participants were escorted to a separate room in which a second, longer investigative interview occurred. 3 There were consequences to being believed and manipulation checks verified that participants were emotionally elevated during the experiment (differentially for truthtellers and liars) and that the stakes were perceived on a moderate-high level in all studies (for more information see Hwang & Matsumoto, 2020;, 2018b, 2019b.…”
Section: Methodsmentioning
confidence: 99%
“…Also, self-report rapport ratings by individuals in an interaction have tended to be unreliable (Abbe & Brandon, 2013;Bernieri, 1988;Bernieri et al, 1994;Tickle-Degnen & Rosenthal, 1990). Studies have reported no correlations between interviewers' and interviewees' self-reported rapport, or between interviewees' self-reported rapport and their own information production (Hwang & Matsumoto, 2020;Matsumoto & Hwang, 2019b).…”
Section: Gaps In the Literaturementioning
confidence: 99%
See 3 more Smart Citations